Role of flower-like ultrathin Co3O4 nanosheets in water splitting and non-aqueous Li–O2 batteries. Issue 21 (23rd May 2018) - Wu, Haitao; Sun, Wang; Shen, Junrong; Rooney, David W.; Wang, Zhenhua; Sun, Kening
Abstract : The bifunctional Co3 O4 nanosheets catalyst in aqueous system promotes the decomposition of DMSO-based electrolyte, resulting in spurious Li–O2 batteries performance. Abstract : The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are both fundamental and essential processes for various energy conversion and storage systems. The kinetics of ORR and OER play a critical role in their energy efficiency and practicality. Here, flower-like ultrathin Co3 O4 nanosheets synthesized through a facile solvothermal technique were studied as a bifunctional catalyst for both water splitting and non-aqueous Li–O2 batteries. Due to the novel structure and highly active {110} and {100} exposed facets, which can effectively facilitate mass transfer and enhance catalytic capability, Co3 O4 nanosheets exhibit better stability and higher ORR/OER activity than Co3 O4 nanoparticles, Co3 O4 bulks, Pt/C, and RuO2 in alkaline solution. More importantly, Li–O2 batteries with ultrathin Co3 O4 nanosheets catalyst can enhance the initial discharge capacity from 6400 to 8600 mA h g −1 and improve the cyclability up to 160 cycles at 500 mA g −1 . Unexpectedly, XRD and UV/Vis techniques suggest that the main product in Co3 O4 nanosheets based cathodes is LiOH, with resulting LiOH also demonstrating reversible formation/decomposition behavior, rather than Li2 O2 in pure Super P based cathodes. Further investigation confirms that Co3 O4 can also catalyze the electrolyte decomposition responsible for the formation of LiOH, and a reaction mechanism was illustrated. This work highlights that the traditional high-efficiency bifunctional catalyst in aqueous media may not be suitable for non-aqueous Li–O2 batteries, and the effect of catalyst on electrolyte besides the discharge product should also be carefully considered for the design of more stable and practical Li–O2 systems.